Interactive Partnership Between Teacher and Parent-Religious Leader to Improve Students’ Attendance and Accomplishment in the Rural Areas - Aloysius Rusmadji; Emiliana Sri Pudjiarti (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to develop a model of school cooperation with parents and religious leaders applied to rural areas, where teachers and religious leaders have a strong influence. This collaboration contains interactive monitoring activities, home learning care, religious leaders' involvement, and students' active participation in classroom learning. The method used in this study is RnD, developed by Gall & Gall., et. al. The instrument validity test was carried out by using the Rcount : Rtable, resulting 0.468. Reliability tests were performed with Alpha Chrombach Estimate, resulting in a reliability coefficient value 0.755. The validity of the contents of the instrument is obtained through the assessment of experts and practitioners. The model's construct validity was tested with the Pearson Correlation Test, while the  effectiveness of the model was tested with the Wilcoxon Test and N-Gain The results of limited tests conducted at SD Inpres Workwana, SD Inpres Pir 2, and SD YPPK Dunumamoy, Keerom Regency, show that the IGOPA model can increase students' active participation in learning. Wilcoxon's test results between before and after the implementation of the IGOPA cooperation model showed significant results, namely the average attendance increased by 25.42%, and the completion of working on tasks increased by 13.28%. The effectiveness of the IGOPA Partnership model yields a value of 0.676 on the N-Gain scale, which means the degree of its significance is medium. The model is only tested in a limited rural area in the Regency of Keerom. It  needs testing in a wider context for its greater validity and effectivity.